Routine testing for group B streptococcus in pregnancy: protocol for a UK cluster randomised trial (GBS3) - Shalini Ojha; Jon Dorling; Stavros Petrou; Soo Downe; Rabia Zill-E-Huma; Sarah Lee; Jane Daniels; Paul Ayuk; Trudy Smith; Lucy Bradshaw; Tracey Cooper; Janine Abramson; et al. (BMJ Open)
Introduction It is unclear whether routine testing of women for group B streptococcus (GBS) colonisation either in late pregnancy or during labour reduces early-onset neonatal sepsis, compared with a risk factor-based strategy.Methods and analysis Cluster randomised trial.Sites and participants 320 000 women from up to 80 hospital maternity units.Strategies Sites will be randomised 1:1 to a routine testing strategy or the risk factor-based strategy, using a web-based minimisation algorithm. A second-level randomisation allocates routine testing sites to either antenatal enriched culture medium testing or intrapartum rapid testing. Intrapartum antibiotic prophylaxis will be offered if a test is positive for GBS, or if a maternal risk factor for early-onset GBS infection in her baby is identified before or during labour. Economic and acceptability evaluations will be embedded within the trial design.Outcomes The primary outcome is all-cause early (<7 days of birth) neonatal sepsis, defined as either a positive blood/cerebrospinal fluid culture, early neonatal death from infection or a negative/unknown culture status with ≥3 agreed clinical signs or symptoms, who receive intravenous antibiotics ≥5 days. All women giving birth ≥24 weeks’ gestation, regardless of mode of birth, and all her babies will be included in the dataset. Cost-effectiveness will be expressed in terms of incremental cost per case of early neonatal sepsis avoided and incremental cost per quality-adjusted life-year associated with each strategy.Ethics and dissemination The trial received a favourable opinion from Derby Research Ethics Committee on 16 September 2019 (19/EM/0253). The allocated testing strategy will be adopted as standard clinical practice by the site. Women in the routine testing sites will give verbal consent for the test. The trial will use routinely collected data retrieved from National Health Service databases, supplemented with limited participant-level collection of process outcomes. Individual written consent will not be sought. The trial results, and parallel economic, qualitative, implementation and methodological results, will be published in the journal Health Technology Assessment.Trial registration number ISRCTN49639731.